Greek Theatre Activities in Germany and Belgium: The Last Fifty Years - Karavia, Maria (Études helléniques / Hellenic Studies, 2008)
From a personal perspective the writer provides an overview of the Greek theatre in Germany since 1960 and in Belgium since 1985. Her account focuses on the contribution of various groups (professional and amateur) in both countries and especially the Greek Theatre of Wuppertal in Germany. Furthermore, there is particular reference to the unique role of the theatre of the Greeks in Germany which attracted many political refugees during the years of the Junta and the subsequent decline which these groups experienced after the political changeover in Greece when many artists repatriated.